GENOTYPIC VARIABILITY, PARTIAL REGRESSION ANALYSIS AND IDENTIFICATION OF EARLY MATURING WHEAT SUITABLE FOR KASHMIR VALLEY - GAZALA HASSAN KHAN, RAKESH VAISHNAVI, ASIF B SHIKARI; Z. A. DAR (The Bioscan, 2015)
Rice wheat cropping system is considered to be a key to food security in India. However, under temperate parts of north-west Himalayas like Kashmir, none of the wheat varieties have been found suitable for cultivation after rice is harvested. The initiative was taken to identify early maturity and high yielding genotype that could fit in Rice-Wheat cropping system. Twenty five wheat genotypes including two checks viz. SKW-355 and HS-240 were evaluated for early maturity, yield and its contributing traits. The analysis of variance revealed presence of significant variability among the genotypes for all the traits studied. Genotypic correlation coefficients revealed significant and positive association of grain yield with number of effective tillers m-1 (0.91), number of spikelets spike-1 (0.70), grains spike-1 (0.92) and 1000-grain (0.97) and negative significant correlation with plant height (-0.37), suggesting that selection of such traits may be rewarding in improving yield. Path coefficient analysis was carried out with grain yield plot-1as response trait. Days to heading showed highest positive direct effect (2.71) on grain yield plot-1 followed by grain filling period (2.23) and 1000-grain weight (0.66). Four genotypes viz., SKW- 355, HPW-366, UP-2831 and HPW-367 matured in 221.33, 225.00, 225.33 and 226.66 days, respectively and recorded the grain yield of 31.11, 22.22, 31.77 and 23.03 q ha-1 respectively thus were found suitable for cultivation under rice-wheat cropping system in Kashmir.